A clinical study on efficacy of peri-lesional autologous platelet-rich plasma in non-healing ulcers - Gogineni, Raghuveer Chakravarthy; Bommareddy, Ratta Reddy; Naresh Babu, Ede; Subhashini, Mayanam; Jaya Krishnah, Akula V. S. (International Surgery Journal, 2022)
Background: Non-healing ulcers are a major health problem worldwide and have a great impact at personal, professional, and social levels. They are a major cause of non-traumatic lower limb amputations. The application of autologous Platelet Rich Plasma (PRP) has been a breakthrough in the treatment of non-healing ulcers, as it is an easy and cost-effective procedure, and provides the necessary growth factors that enhance tissue healing. The aim and objective of the study was to test the effectiveness of peri-ulcer autologous platelet-rich plasma injection in chronic non-healing ulcers and to assess the time taken for wound closure. Methods: This study was conducted on 50 patients during the period of November 2020 to October 2021 from the in-patients of the surgical unit in Dr. PSIMS and RF. Autologous PRP was prepared from whole blood utilizing a rapid, point-of-care system that works on the principle of density gradient centrifugation. Fifty (50) patients with non-healing ulcers of different etiologies, who met the inclusion criteria, were treated with peri-ulcer autologous PRP injections once weekly. Results: Of the 50 cases 29 were male and 21 were female, the mean age of the patients is 54.48±10.79 years. All the patients showed signs of wound healing with a reduction in wound size, and the mean time duration of ulcer healing was 6.75±1.47 weeks. Conclusions: This prospective study has demonstrated the potential safety and efficacy of autologous platelet-rich plasma injection for the treatment of chronic non-healing ulcers.